MODELING & SIMULATION IN PROCESS SYSTEMS ENGINEERING - Nor Alafiza Yunus; Zarina Ab Muis; Azizul Azri Mustaffa; Haslenda Hashim; Mazyar Madooi; Mohd. Shukri Mat Nor; Nik Nurul Norfatiha N Mohd. Zahari; Nor Alafiza Yunus; Sharifah Rafidah Wan Alwi; Siong, King Yuan; Theo, Wai Lip; Zainuddin Abdul Manan; et al. (Johor Bahru, Johor : Penerbit UTM Press, 2016)
Includes bibliographical references and index